Effect of chloramphenicol on DNA repair synthesis in fetal liver cells of rats - Wang Ai-ping; Wang Xiao-peng (Acta Pharmacologica Sinica; Vol 10, No 6 (November 1989): Acta Pharmacologica Sinica, 2016)
The inhibitory effect of chloramphenicol (CAP) on the DNA repair synthesis were studied on a primary cell culture of fetal liver tissue of rats. The fetuses were taken out with the umbilical cords and the placenta: then, the fetal livers were injected with a balanced salt solution and Type I collagenase through the umbilical vein. At the same time, the blood of the fetal livers were drained through the umbilical artery. The cells were detached at 10 degrees C with a steel mesh. Chloramphenicol 1.6-403.8 mmol/L did not show significant increase in DNA repair synthesis. The unscheduled DNA synthesis (UDS) was active when the positive control 7,12-dimethylbenzanthrancene(DMBA) was added alone to the culture in autoradiographic assay, but it was inactive when DMBA was added together with CAP. Therefore, it may be assumed that CAP has an inhibitory effect on the DNA repair synthesis.